IMPLEMENTASI AKAD HAWALAH PADA TRANSAKSI OVER KREDIT MOTOR DALAM PERSPEKTIF FATWA DSN-NO: 12/DSN-MUI/IV/2000 (STUDI KASUS DI KECAMATAN KRONJO KABUPATEN TANGERANG) - Ariftullah, Muhamamd; Jamaluddin, Jamaluddin; Masduki, Masduki (STAI Darul Qalam Tangerang, 2023)
The hawalah contract is a transfer of debt from party to party and is included in the tabbarru contract, which is a helping contract that aims solely to expect the blessings of Allah Almighty, not to seek profit. During this pandemic, the community really felt the impact in the economy, because several companies or industrial factories as the source of the community's economy went out of business and carried out mass layoffs. This encourages people to find ways to meet their needs, because they have dependents with leasing companies, because people do not want to take risks, then over-credit is carried out. Over-crediting a motorbike is an effort to solve the problem of bad motorcycle loans. However, the practice in the field is not in accordance with the rules of Islamic law and positive law. Because the over-credit transaction activities do not involve the debtor, namely leasing only involves two parties, namely the first party (muhil) and the third party (muhal 'alaih). Based on the background above, the formulation of the problems in this study, is: 1) How is the implementation of the hawalah agreement in the over-credit transaction of the motorbike in Kronjo District, Tangerang Regency? 2) What is the practice of over-crediting motorbikes based on the Fatwa of the National Sharia Council No:12/DSN-MUI/IV/2000? 3) How is the review of the Fatwa of the National Sharia Council No: 12 / DSN / MUI / 2000 against over-crediting of motorcycles in Kronjo District, Tangerang Regency? This study aims to 1) To determine the implementation of the hawalah contract in over-credit transactions in Kronjo District, Tangerang Regency. 2) To find out the practice of over-crediting motorcycles based on the Fatwa of the National Sharia Council No:12/DSN-MUI/IV/2000. 3) To inform the review of the Fatwa of the National Sharia Council No: 12 / DSN / MUI / 2000 against over-crediting of motorcycles in Kronjo District, Tangerang Regency. This research uses a type of qualitative research method to examine data from (field research) research conducted by going directly to the field. The conclusion is that the implementation of the hawalah agreement against over-credit in Kronjo District is not in accordance with the Fatwa of the National Sharia Council No:12/DSN-MUI/IV/2000. Because it does not meet the pillars and contains gharar, in the transaction the leasing party is not confirmed by the first (muhil) and third (muhal 'alaih) parties in the over-credit motorbike transaction in Kronjo District